Challenging the Curious Erasure of Religion from the Study of Religious Terrorism - Dawson, Lorne L. (Numen, 2018)
The role that religion plays in the motivation of “religious terrorism” is the subject of much ongoing dispute, even in the case of jihadist groups. Some scholars, for differing reasons, deny that it has any role; others acknowledge the religious character of jihadism in particular, but subtly discount the role of religion, while favoring other explanations for this form of terrorism. Extending an argument begun elsewhere (Dawson 2014, 2017), this article delineates and criticizes the influence of a normative religious bias, on the one hand, and a normative secular bias, on the other hand, on scholarship addressing the relationship between religiosity and terrorism. I examine two illustrative studies to demonstrate the complexity of the conceptual issues at stake: Karen Armstrong’s best-selling book Fields of Blood: Religion and the History of Violence (2014) and a recent article by Bart Schuurman and John G. Horgan on the rationales for terrorist violence in homegrown jihadist groups (2016).